Weight-based combination therapy with peginterferon alpha-2b and ribavirin for Naïve, relapser and non-responder patients with chronic hepatitis C - Fernando Lopes Gonçales Jr.; Aline Vigani; Neiva Gonçales; Antonio Alci Barone; Evaldo Araújo; Roberto Focaccia; Umbeliana Oliveira; Henrique Sérgio Morais Coelho; Jacqueline Paixao; Renata Perez; Cirley Lobato; Judith Weirich; et al. (Brazilian Journal of Infectious Diseases)
Combination therapy with pegylated interferon and ribavirin is considered the new standard therapy for naïve patients with chronic hepatitis C. We evaluated the efficacy and safety of treatment with weight-based peginterferon alpha-2b (1.5 mg/kg per week) plus ribavirin (800-1,200 mg/day) for 48 weeks in naïve, relapser and non-responder (to previous treatment with interferon plus ribavirin) patients with chronic hepatitis C. Sixty-seven naïve, 26 relapser and 40 non-responder patients were enrolled. The overall sustained virological response (SVR) for the intention-to-treat population was 54% for naïve, 62% for relapser and 38% for non-responder patients. In the naïve subgroup, SVR was significantly higher in patients with the non-1 genotype (67%) compared to those with genotype 1 (45%). In relapsers and non-responders, SVR was, respectively, 69% and 24% in patients with genotype 1 and 43% and 73% in those with genotype non-1. There were no significant differences in SVR rates among the three body weight ranges (< 65 kg, 65-85 kg and > 85 kg) in any of the subgroups. Early virological response (EVR) was reached by 78%, 81% and 58% of naïve, relapser and non-responder patients, respectively, and among those with EVR, 63%, 67% and 61%, respectively, subsequently achieved SVR. All of the non-responder patients who did not have EVR reached SVR. Treatment was discontinued in 13% of the patients, due to loss to follow-up, hematological abnormalities or depression.